Understanding China's growing influence in global data governance - Erie, MS; Streinz, T (US-Asia Law Institute blog, 2021)
The Trump Administration’s moves to ban the Chinese-owned apps TikTok and WeChat in the United States out of concerns that the data of U.S. citizens could be shared with the Chinese government have been extensively discussed. What is less debated—or, for that matter, even understood—is China’s influence on data governance globally, particularly in developing countries. China’s impact is likely to be more significant in emerging economies where Chinese tech companies are supplying information and communications technology, e-commerce platforms, and digital surveillance technology, than in the US or European Union.